Primary Pronunciation Box. Pronunciation games and activities for younger learners + CD - Nixon, Caroline; Tomlinson, Michael (Cambridge Cambridge University press, 2010)
In this book, elements of pronunciation are practised through a range of exciting songs, rhymes, chants, games, word searches, crosswords and other task-based activities to introduce children to English pronunciation.
Contents.
Keywords: Language; Learning; Activities; Games; English - foreign language